Improvement of the blockchain protocol based on memory-hard function - Sui CHENG; Xianzheng LIN; Nenghai YU (网络与信息安全学报)
A new blockchain chain protocol was proposed,which allowed adjusting the loading time of the mining process.This strategy reduced the ASIC and CPU mining rate of the gap,so that the using of ASIC mining is limited.Finally,the safety of this new chain structure was analyzed and compared to the original chain protocol.